MarA, SoxS and Rob of Escherichia coli – Global Regulators of Multidrug Resistance, Virulence and Stress Response - Duval, Valérie; Lister, Ida M. (International Journal of Biotechnology for Wellness Industries, 2013)
Bacteria have a great capacity for adjusting their metabolism in response to environmental changes by linking extracellular stimuli to the regulation of genes by transcription factors. By working in a co-operative manner, transcription factors provide a rapid response to external threats, allowing the bacteria to survive. This review will focus on transcription factors MarA, SoxS and Rob in Escherichia coli, three members of the AraC family of proteins. These homologous proteins exemplify the ability to respond to multiple threats such as oxidative stress, drugs and toxic compounds, acidic pH, and host antimicrobial peptides. MarA, SoxS and Rob recognize similar DNA sequences in the promoter region of more than 40 regulatory target genes. As their regulons overlap, a finely tuned adaptive response allows E. coli to survive in the presence of different assaults in a co-ordinated manner. These regulators are well conserved amongst Enterobacteriaceae and due to their broad involvement in bacterial adaptation in the host, have recently been explored as targets to develop new anti-virulence agents. The regulators are also being examined for their roles in novel technologies such as biofuel production.